2015
DOI: 10.1002/2014gc005611
|View full text |Cite
|
Sign up to set email alerts
|

Radial fast‐neutron fluence gradients during rotating40Ar/39Ar sample irradiation recorded with metallic fluence monitors and geological age standards

Abstract: Characterizing the neutron-irradiation parameter J is one of the major uncertainties in 40 Ar/ 39 Ar dating. The associated uncertainty of the individual J-value for a sample of unknown age depends on the accuracy of the age of the geological standards, the fast-neutron fluence distribution in the reactor, and the distances between standards and samples during irradiation. While it is generally assumed that rotating irradiation evens out radial neutron fluence gradients, we observed axial and radial var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…[] detailed the analytical procedures for the ALF laboratory, and Rutte et al . [] detailed the irradiation geometry and reactor specifics used for the ALF samples, which comprise the majority of the reported ages; additional to age standards, metallic fluence monitors were used to correct for horizontal fluence gradients in some irradiations (Table S2). We used the revised age‐standard values of Renne et al .…”
Section: Methodsmentioning
confidence: 99%
“…[] detailed the analytical procedures for the ALF laboratory, and Rutte et al . [] detailed the irradiation geometry and reactor specifics used for the ALF samples, which comprise the majority of the reported ages; additional to age standards, metallic fluence monitors were used to correct for horizontal fluence gradients in some irradiations (Table S2). We used the revised age‐standard values of Renne et al .…”
Section: Methodsmentioning
confidence: 99%
“…(9) Irradiation parameter (J): The parameter J, which quantifies the production of 39 Ar from 39 K in the age equation, is determined by analyzing a co-irradiated fluence monitor with accurately known age. The J value varies horizontally and vertically in an irradiation stack due to neutron flux gradients in the reactor (e.g., Rutte et al, 2015), which can be quantified by analyzing numerous fluence monitors interspersed with the samples at known positions relative to each other.…”
Section: Data Corrections and Factors Contributing To Uncertaintiesmentioning
confidence: 99%
“…However, given the finite spatial extent of the pits, the fluence gradient adds to the variance of the F values within each pit. Rutte et al (2015) showed that the three--dimensional variation of neutron fluence in a reactor core is expected to be the result of superposing inverse--square and exponential decay functions. However, over the small extent of the irradiation discs a planar fit is a good first order approximation with residuals of <0.3%, and mostly <0.1%.…”
Section: Sample Preparationmentioning
confidence: 99%